Occupational Safety and Health Risk Management: A Practical Approach - Hashim, A. H. (2014)
Occupational safety and health (OSH) strive to reduce (or ideally eliminate) any form of injury, illness or damages to human capital and assets.Low rates of injury, illness and damage can improve organization’s reputation and worker’s morale, increase productivity,money stays where it should be or spent at areas needed most.OSH is increasingly a best practice at best companies/organization, simply a mark of civilized community. Risk assessment is a major component in managing occupational safety and health. The lecture focuses on how risk assessment is done in a practical way.